An economical ultrasonic-assisted extraction for the spectro- photometric determination of anionic surfactants - Sarawut Somnam (2018)
An economical ultrasonic-assisted extraction system was developed for the extraction/spectrophotometric determination of anionic surfactants based on methylene blue method. A low- cost ultrasonic cleaner was employed to enhance extraction efficiency and also to reduce chemical consumption, time and cost of analysis. Optimum conditions for extraction and detection were determined. Extraction time of 30 seconds and a volume ratio of aqueous sample to organic solvent of 8:1 were found to be optimum. Concentrations of methylene blue and Na2SO4 were selected at 10-5 and 10-2 M respectively. Simultaneous parallel extraction of 12 samples could be carried out. Standard solutions of sodium dodecyl sulphate (0.10 mg L-1) were evaluated for reproducibility and the relative standard deviation was found to be 4.8%. The method was applied to the analysis of 7 real water samples. The concentrations of AS were found in the range of 0.054-0.123 mg L-1. The results obtained were compared to those from the standard method and no significant difference was observed. Recovery was found to be 106-112%. © 2011 by Maejo University, San Sai, Chiang Mai, 50290 Thailand.